Synthesis, Spectral Characterization, Theoretical Evaluation of New Cu (II) and Ni (II) Complexes of Flavon - Omar H. Al-Obaidi (Journal of Global Pharma Technology, 2016)
A new series of Cu (II) and Ni (II) complexes with the Flavone ligand were prepared and spectroscopic method and elemental analysis verified their structures. All the prepared complexes have been identified by available spectroscopic tools (UV-Visible and IR) in addition the structure of complexes was characterized by magnetic moments and molar conductance in DMSO solution .From the above of these studies and measurements suggest an tetrahedral geometry around Cu(II) and Ni(II). A theoretical treatment of the formation of complexes in the gas phase was studied; this was done using the Hyperchem-6 program for the Molecular mechanics and Semi-empirical calculations. Keywords: Flavone, Metal complexes, Synthesis, Spectral, Theoretical Evaluation.